2013
DOI: 10.1111/ijfs.12253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analytical methods for measuring proanthocyanidins in wines and their relationship with perceived astringency

Abstract: Artículo de publicación ISIThe concentration of proanthocyanidins from twenty red wines from cv. Cabernet Sauvignon, five ros e wines from cv. Cabernet Sauvignon and five white wines from cv. Sauvignon Blanc was quantified using four analytical methodologies, and their relationship with the perceived astringency was investigated. Proanthocyanidin concentrations were determined by a methylcellulose precipitation assay, a protein precipitation assay and two colourimetric methods (Bate-Smith and vanillin assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
4
29
1
Order By: Relevance
“…On the other hand, the comparison of both precipitations based methods has shown that MCP tannin values are on average three time higher than those found for BSA. However, a strong correlation (0.8) between the values obtained with the two methods has also been reported [42], whereas no correlation was observed between these two methods and the tannin content obtained with the acid hydrolysis method [37]. Finally, despite the differences in absolute values, attributable to the differences in both procedures, it has also been stated that both precipitants (BSA and MCP) precipitate the same amount of tannins when tested under the same conditions [39,43].…”
Section: Total Tannin Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the comparison of both precipitations based methods has shown that MCP tannin values are on average three time higher than those found for BSA. However, a strong correlation (0.8) between the values obtained with the two methods has also been reported [42], whereas no correlation was observed between these two methods and the tannin content obtained with the acid hydrolysis method [37]. Finally, despite the differences in absolute values, attributable to the differences in both procedures, it has also been stated that both precipitants (BSA and MCP) precipitate the same amount of tannins when tested under the same conditions [39,43].…”
Section: Total Tannin Contentmentioning
confidence: 99%
“…The total tannin content is in this case estimated as epicatechin equivalents. In addition, one of the main benefits of precipitation based methods is that a theoretic positive correlation with astringency intensity is foreseen [37][38][39]. The hypothesis is based on the assumption that the method simulates the phenomena that naturally occurs in wine when it becomes in contact with the salivary proteins.…”
Section: Total Tannin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…• Classic tannin analyses rely on condensation reactions with aldehydes such as vanillin to yield a colored product [26]. These approaches will detect monomers as well, and are not often reported for wine analysis.…”
Section: Proanthocyanidin Concentrations and Measurements In Grapes Amentioning
confidence: 99%
“…Following precipitation, the phenolic content of the pellet or supernatant can be measured. These precipitation methods can achieve very high correlations between "astringency intensity" and "tannin" (r 2 > 0.8), likely because they mimic reactions that would occur between tannins and lubricating salivary proteins in the mouth [7]. …”
Section: Introductionmentioning
confidence: 99%